2020
DOI: 10.1007/s42452-020-03634-w
|View full text |Cite
|
Sign up to set email alerts
|

Energy-saving method of heat transfer enhancement during magneto-thermal convection in typical thermal cavities adopting aspiration

Abstract: In the area of energy-efficient system development, the paper presents a novel approach aiming to enhance heat transfer during magnetohydrodynamic convection in thermal cavities by implementing a technique of free aspiration. Through two small openings, the proposed free aspiration naturally allows a partial admission of fresh fluid into the cavity (from its immediate surroundings) and eventually vents the admitted fluid out the cavity without any pumping device. The efficacy of aspiration technique, whether v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 39 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…Chakravarty et al [21] numerically examined the influence of a ventilation method and, the furnishing side injection of cold fluid by the face of the enclosure, on heat management by using the thermal non-equilibrium approach. A novel method was evinced by Bioswas et al [22] in order to enhance heat transfer in thermal enclosures assuming aspiration. It was reported that the heat transfer was ameliorated in all three enclosures owing to aspiration.…”
Section: Introductionmentioning
confidence: 99%
“…Chakravarty et al [21] numerically examined the influence of a ventilation method and, the furnishing side injection of cold fluid by the face of the enclosure, on heat management by using the thermal non-equilibrium approach. A novel method was evinced by Bioswas et al [22] in order to enhance heat transfer in thermal enclosures assuming aspiration. It was reported that the heat transfer was ameliorated in all three enclosures owing to aspiration.…”
Section: Introductionmentioning
confidence: 99%
“…The findings show that the mechanism of mixed convectives considerably depends on the considered magnetic field inclination angle, bioconvection Rayleigh number, and Richardson number. Biswas et al 43 presented a novel method for improving the heat transfer through MHD convection inside cavities using the free aspiration technique. The developed equations model has been derived using the Maxwell model (for magnetic fields) and the Brinkman–Forchheimer–Darcy model (for porous media).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning air‐filed enclosures ( Pr = 0.71), the authors found a symmetric flow structure regardless of the Rayleigh number within the studied range. Biswas et al 5 presented an innovative approach for improving magnetohydrodynamic convection heat transfer in thermal cavities by deploying a technique of free aspiration. The authors have demonstrated that a free aspiration system can enhance heat transfer significantly without the need for pumping effort.…”
Section: Introductionmentioning
confidence: 99%
“…It is also noted from the literature review that there is no relationship linking the first and the second laws of thermodynamics except for general definitions. The efficiency of a system was either assessed based on the first law (heat transfer coefficient and Nusselt number), for instance, Biswas et al 5 or the entropy production derived from the second law of thermodynamics. However, the numerical relationship between the first two laws has not been discussed from a numerical viewpoint.…”
Section: Introductionmentioning
confidence: 99%